Beacon Lights of History, Volume 14: The New Era : A Supplementary Volume, by Recent Writers, as Set Forth in the Preface and Table of Contents - Lord, John, 1810-1894 (Salt Lake City, UT : Project Gutenberg, 2004)
"Beacon Lights of History, Volume 14: The New Era" by John Lord is a historical account likely written in the late 19th century. This volume serves as a supplementary work, showcasing significant achievements and figures from the latter half of that century, particularly those who revolutionized various fields such as music, art, philosophy, and science. The text highlights notable individuals like Richard Wagner in the realm of music and John Ruskin in art, portraying them as "Beacon Lights" of progress and development during a period marked by rapid transformation and intellectual growth. At the start of the book, the focus is primarily on the contributions and journeys of Richard Wagner as a composer. The narrative explores Wagner's early life, struggles, and eventual successes, detailing how he overcame initial obstacles and criticisms to establish himself as a pivotal figure in the evolution of opera. The opening emphasizes the formative influences on Wagner's work, highlighting his relationships with other musicians and the cultural context of his time. This introductory portion sets the stage for deeper explorations of individual accomplishments and their lasting impacts on society and the arts in the following sections of the volume. (This is an automatically generated summary.)
Release date is 2004-01-01
E-text prepared by Juliet Sutherland, Charlie Kirschner, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: History